De Entvölkerung des Apennins 1961-1971. Eine Kartenerläuterung - Rother, Klaus; Wallbaum, Ursula (ERDKUNDE, 1975)
Population changes in the Apennines during the 1960s are reported. Comparisons with Tichy's map of the previous decade shows that the size and spatial effect of the flight from the mountains had remained similar. Only in the extreme south was there a stronger movement between 1961 and 1971.